Parental Guidance and Digital Media Shaping Early Childhood Digital Literacy - Hidayatussoalihah Hidayatussoalihah; Edy Herianto; MA Muazar Habibi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid advancement of digital technology has transformed how young children learn and interact with information, emphasizing the need to develop digital literacy from an early age. Specific Background: In Indonesia, where internet access among children continues to grow, parental guidance and appropriate digital media use play crucial roles in shaping responsible and skillful digital engagement. Knowledge Gap: However, prior studies have predominantly examined these factors separately, lacking insight into their combined influence on early childhood digital literacy. Aims: This study aims to analyze the relationship between parental guidance and digital media use—individually and jointly—on the digital literacy skills of children aged 4–6 years. Results: Using a quantitative correlational design with 32 parent-child pairs, results revealed significant positive correlations between parental guidance (r = 0.704), digital media use (r = 0.755), and their combined effect (R = 0.757; p < 0.001) on children’s digital literacy. Novelty: The study contributes novel evidence on the synergistic impact of parental involvement and media utilization, integrating both factors within a single analytical model. Implications: These findings highlight that balanced parental supervision and constructive media engagement foster optimal digital literacy development in early childhood, supporting safer and more educational technology use. Highlights: Parental involvement significantly enhances children’s digital literacy skills. Balanced digital media use fosters safe and educational technology engagement. The synergy of guidance and media utilization yields optimal literacy outcomes. Keywords: Parental Guidance, Digital Media, Digital Literacy, Early Childhood